Some vascular epiphytes on mango and their control - Lim, Tong Kwee; Khoo, Khay Chong (Incorporated Society of Planters, 1985)
The vascular epiphytes comprising the ferns, orchids and semi-parasitic mistletoes are a common sight in neglected orchards and bud wood nurseries, and on the branches and trunks of old and un tended mango trees in villages and roadsides. Together with the cryptogamic epiphytes like the mosses, liverworts and lichens, they form a unique ecological community on wild and cultivated trees. They thrive in partially shaded positions, growing in cracks and crevices in the bark and at the fork of the trunk and branches and sometimes extending onto the leaves. Despite their ubiquity, their presence on mango and other cultivated trees has often been dismissed as unimportant, hence the dearth of local information available. Most published information on such epiphytes pertains to their taxonomy and botany. Significant contributions in these aspects of the vascular epiphytes have been rendered by Holttum (1964)' on orchids; Sands (1924) on mistletoes; Holttum (1966) and Johnson (1977) on ferns. The aim of this paper is to assess the occurrence, significance. And the control of such epiphytes in relation to mango cultivation. To aid in identification of the epiphytes a brief botanical description is also included.